How Neighborhoods Influence Health: Lessons to be learned from the application of political ecology. (May 2017) - Chitewere, Tendai; Shim, Janet K.; Barker, Judith C.; Yen, Irene H.
Abstract: AIM: This paper articulates how political ecology can be a useful tool for asking fundamental questions and applying relevant methods to investigate structures that impact relationship between neighborhood and health. Through a narrative analysis, we identify how political ecology can develop our future agendas for neighborhood-health research as it relates to social, political, environmental, and economic structures. Political ecology makes clear the connection between political economy and neighborhood by highlighting the historical and structural processes that produce and maintain social inequality, which affect health and well-being. These concepts encourage researchers to examine how people construct neighborhood and health in different ways that, in turn, can influence different health outcomes and, thus, efforts to address solutions.